Eight Emerging Effects of the COVID-19 Pandemic on Small-Scale Cross-Border Trade in the Great Lakes Region - Mvunga, Nyembezi; Kunaka, Charles (World Bank, Washington, DC, 2021)
Small-scale cross-border trade (SSCBT) is a defining feature of the economies of the borderlands of the Great Lakes Region (GLR). It is an important source of income and a necessary channel to access goods and services that have enabled vulnerable households to increase their resilience against outside shocks and escape extreme poverty. SSCBT enhances food security and contributes to improved stability in this conflict-afflicted region. However, the Coronavirus (COVID-19) pandemic, which has resulted in the restricted movement of people, goods, and services across borders in the GLR since March 2020, has greatly affected informal cross-border trade and traders. Its persistence has also hindered the progress that countries in this region have made toward improving the trading environment. Evidence from the World Bank’s Great Lakes Trade Facilitation Project (GLTFP), which has been undergoing implementation in the Democratic Republic of Congo (DRC), Rwanda, Uganda, and the Common Market for Eastern and Southern Africa (COMESA) since 2015, highlights to a greater extent how the pandemic has erased some of the progress that countries in the region have made toward improving the livelihoods of their citizens and the trading environment. The objective of this note is to provide evidence of some of the emerging effects of the Coronavirus (COVID-19) pandemic on SSCBT in the GLR. Because the effects of the pandemic are still evolving, this note summarizes emerging patterns that can inform discussions on policy response and the design of measures to lessen the effect of the pandemic and help protect the future of small-scale trade in the region. This note presents the emerging effects of the pandemic in the region as evidenced by the GLTFP, and is followed by recommendations on focus areas for policy makers.